A New Pleurothallis from Colombia, with a Note on Ancipitia and Colombiana (Orchidaceae: Pleurothallidinae) - Rodríguez Martínez, Lizeth (2015)
A new species of Pleurothallis from Valle del Cauca, Colombia, is described and illustrated. Pleurothallis ottocari is similar to the Ecuadorian P. scoparum, but differs in the widely elliptic leaf, the smaller flowers, the incurved dorsal sepal, the purplish-tinted petals, which are conspicuously curved downwards above the middle, and the basally sub-truncate lip. Brief comments are given as to the reason for not using the generic names Ancipitia and Colombiana, to which the new species would otherwise belong.